2022
DOI: 10.1111/sjop.12819
|View full text |Cite
|
Sign up to set email alerts
|

Social comparison orientation mediates the association between HEXACO and self‐presentation

Abstract: Various researchers have investigated the personality correlates of defensive and assertive self‐presentation. Yet, only a few studies go beyond the direct relationships and examine the underlying mechanism. The current study examines whether the social comparison orientation (SCO) mediates the relationship between personality and self‐presentation. We also tested whether our proposed model is invariant across genders. We collected data from 496 individuals using the HEXACO personality inventory, the self‐pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
1
0
1
Order By: Relevance
“…In addition, there are studies researching self-objectivation of women which involved approval motivation in self-presentations in the Internet (Chen et al, 2022) and the impact of women's self-esteem on a self-presentation strategy in social networks . The research by S. Demir et al (2022) found that orientation toward social comparison determines a correlation between an individual and self-presentation. C. You et al (2022) think that permanent improvement of self-presentation in social networks can cause psychological addiction.…”
Section: Antonina Hrys* Oksana Pavliukmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are studies researching self-objectivation of women which involved approval motivation in self-presentations in the Internet (Chen et al, 2022) and the impact of women's self-esteem on a self-presentation strategy in social networks . The research by S. Demir et al (2022) found that orientation toward social comparison determines a correlation between an individual and self-presentation. C. You et al (2022) think that permanent improvement of self-presentation in social networks can cause psychological addiction.…”
Section: Antonina Hrys* Oksana Pavliukmentioning
confidence: 99%
“…Цей перелік доповнюють дослідження, у яких відстежують самооб'єктивацію жінок, що передбачала мотивацію схвалення в самопрезентаціях всемережжя (Chen et al, 2022) та вплив жіночої самооцінки на стратегію самопрезентації в соціальних мережах . У дослідженні S. Demir et al (2022) з'ясовано, що орієнтація на соціальне порівняння опосередковує зв'язок між особистістю та самопрезентацією. Постійне вдосконалення самопрезентації в соціальних мережах може викликати психологічну залежність, на думку C. You et al (2022).…”
Section: Antonina Hrys* Oksana Pavliukunclassified